Cytotoxic activity of isolate compounds from derendan (Lansium parasiticum (Osbeck) K.C. Sahni & Bennet) fruit peel - Fadhli, Haiyul; Rahmayanı, Wıky; Allaya, Regina; Jumadila, Ikhsal Mukri; Fernando, Armon; Utami, Rahayu (Faculty of Pharmacy, Universitas Pancasila, 2024)
Derendan (Lansium parasiticum (Osbeck) K.C. Sahni & Bennet) is a plant from the Meliaceae family that grows in the tropics, especially in Sumatra (Indonesia). It was reported that this plant has antimalarial, antimutagenic, and anticancer properties. This study aims to determine the cytotoxic activity of compounds isolated from the methanol extract of Lansium parasiticum bark. Extraction using maceration method with methanol solvent. Vacuum Liquid Chromatography (KVC) with 21 different eluent ratios (n-hexane : ethyl acetate and ethyl acetate ; methanol) was utilized for the fractionation. The result was 21 fractions. The washing technique was used to purify fraction 17. The obtained compound LPR17 with a melting point of 239-241ᵒC. Based on the UV spectrum, the wavelengths of the LPR17 compound were 277.0 nm and 205.0 nm. The FT-IR spectrum shows aliphatic OH, CH, C=O, C-H, and C-C functional groups. This compound reacts positively with the Liebermann-Burchard reagent. The compound obtained is a triterpenoid group. Cytotoxic test using BSLT method. LPR17 compounds provide very strong cytotoxic activity (LC50 = 67.15 g/mL).